Shoot complexes on the apical part of the crown of generative Fraxinus excelsior L. trees - I. S. Antonova; M. S. Televinova (Труды по прикладной ботанике, генетике и селекции, 2024)
Background. Fraxinus excelsior L. is a common forest species in the Central Russian Upland, used to produce valuable lumber and for landscaping. Mass mortality of this species due to fungi and insects determines the relevance of its detailed research. Tree crown development features play an important role in the tree’s life in both dense communities and open spaces.   Materials and methods. Shoots and large branches were collected from the apical part of the crown for ten years in Belgorod and Leningrad Provinces. The lengths of internodes and shoots, the numbers of leaves and branchings, and shoot development patterns were analyzed. An unmanned aerial vehicle was employed to examine the treetops. The complexes of large branches on the crown periphery in different age states (g1, g2, and g3) were studied both by direct measurement and using photographs. The effect of temperatures on the length and number of leaves was assessed with a two-way analysis of variance (ANOVA).   Results. Shoots of F. excelsior are significantly shorter at high mean temperatures in the second ten-day period of June. The number of leaves on them is significantly greater at high temperatures in the second ten-day period of May. Six-to-eight-leafed shoots make up the ascending part on the curve of the sequence of internode lengths for the most developed shoots. In ontogenetic states g1 and g2, the crown surface is represented by sections of large branches. In the g3 state, they break up into complexes of small weakly branching spherical structures. The apical branches of the umbrella-shaped crown of generative ash trees are inverted cone-shaped shoot complexes with a similar development pattern.   Conclusion. The structure and development of F. excelsior branches characterizes the ecological features of the species, manifested through the absence of obvious branching orders and combined with the inverted conical shape of large branches.